Efeito agudo da vibração mecânica de corpo inteiro sobre o desempenho do chute semicircular no karaté - Salinas, Johan Andrés Robalino (2023)
During a kumite competition, the use of the semicircular kick known as mawashi geri provides advantages to competitors. To optimize its efficiency before training or competition, it is essential to reach an optimal level of muscle warm-up to achieve the best possible performance. Research in the field of Sports Science has shown that the inclusion of a conditioning activity (CA) before the main activity results in an increase in overall test performance. This phenomenon is known in the literature as PostActivation Potentiation (PAPE). Whole-body vibration (WBV) has emerged to activate PAPE in different motor tasks and may contribute to performance in executing the kick. However, accurate evaluation of specific kinetic and kinematic variables of the kick still presents a challenge. Therefore, the objective of this study was to develop a technological device capable of quantifying the kinetic and kinematic variables of the semicircular kick in karate-do and to verify the acute effects of WBV on the semicircular kick. To test the reliability of the developed device, 24 male karate-do athletes participated in the medium semicircular kick test, in which impact force, impulse, attack time, contact time, and return time variables were collected. The participants returned to the laboratory 48 hours later to perform a retest. In addition, to evaluate the effects of WBV, 16 athletes were divided into two conditions: no whole-body vibration (NWBV) and with WBV. In the WBV condition, volunteers were exposed to a vibration session consisting of four sets of one minute vibration and one minute rest between sets. For each set, the platform was adjusted to a frequency of 26 Hz and an amplitude of 4 mm. In the NWBV condition, athletes performed the same protocol with the vibrating platform turned off. All data were presented as mean, standard deviation, and standard error of measurement. To verify the reliability of the device, Pearson's correlation was used for the test and retest variables. In addition, a t-test and intraclass correlation coefficient (ICC) were performed. To verify the acute effects of WBV, a two-factor repeated measures analysis of variance (ANOVA) was performed and the smallest worthwhile change (SWC) was presented. The significance level adopted was p ≤ 0.05. The calibration of the constructed system showed a correlation of tension and force in kilograms for load cells A=0.99; B=0.99; C=0.99; D=0.99. In the t-test comparison, the p-values and ICC were as follows: impact force p=0.82; ICC=0.93; impulse p=0.75; ICC=0.93; attack time p=0.76; ICC=0.70; contact time p=0.50; ICC=0.60; return time p=0.83; ICC=0.71 and total time p=0.80; ICC=0.77. The p-values presented in the comparison between conditions in the ANOVA and SWC are, respectively, as follows: impact force: p=0.82; SWC=180.44, impulse: p=0.97; SWC=2.07, attack time: p=0.02; SWC=0.006, contact time: p=0.142; SWC=0.00, return time: p=0.571; SWC=0.018 and total time: p=0.78; SWC=0.02. The results showed high reliability and accuracy of the evaluation variables generated by the semicircular kick. The observed difference in the attack phase between NWBV and WBV conditions suggests that.